Mudhorobah At Micro Small Medium Enterprise “Small and Strong” - Wahyudi, Heru; Ansori, Muslich (FEB - Universitas Lampung, 2018)
This research aims to find out the self regulating profit and loss sharing (PLS) facing the increase of regional minimum wage (RMW) at micro small and medium enterprise (MSME) in Indonesia. The background of this research the existence of wage conflict and the threat of urgency of MSME due to the policy of RMW. The theory used is the self regulating of Ediorno and theory profit and loss sharing of Ibn kaldun. The method used case study research conducted on MSME PtM in 6 districts in Lampung Province. Based on its explanation level, this study is a descriptive-comparative study. While based on its objectives, this research is applied research . Processed data are PLS of PtM and RMW in Lampung Province. This study is important to show the self regulating profit and loss sharing (PLS) at MSME as solution wage problem. The results showed that; MBM in MSME PtM has self regulating against UMR increase. The results of this study are in line with Ibn Taimyah